Curvature Loss Optical Fiber Analysis of Head Passive Sensor on the Mandrell Fiber - Harry Ramza (Rekayasa Teknologi, 2013)
In this research, the curvature loss of optical fiber had been measured to be used asHead Passive sensors. This measurement produces the data in the form of output powerfrom varying value of curvature radius. The length of optical cable is 2.173 m, the laserpower is 0.53 mW and the power output of focal lens is 0.26 mW. The data obtained isan optical output power with radius of curvature from 1 cm until 20 cm. This will bedetermined curvature coefficient of weakening or loss. A variation of curvature radiusthat was tested from 1 cm to 20 cm with an increment step is 1 cm.